(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
In this research an approximation was achieved, to what digital literacy is, the tools that make it up and the updating of strategies, in the same way some effects that digital literacy causes in students, strategies and teachers were identified. that cannot adapt to digital tools. In the same way, it was taken into account that, through digital literacy, it is possible to obtain new skills, abilities and competencies in students. Therefore, it was taken into account that digital literacy is current, that is, that the components that it entails are housed in a recent change, where an update and changes have to be incorporated to reach a current understanding and achieve adaptation of the called digital literacy